Reasons for extraction of teeth in COVID corona pandemic: a retrospective study - Saikhedkar, Rashmi; Nirwan, Amit Singh; Jain, Samkit (International Journal Of Community Medicine And Public Health, 2023)
Background: Aim and objectives were to evaluate the various reasons for extraction of teeth during corona pandemic time. Methods: A total of 769 patients were selected for the study which included 376 males and 393 females. The study included those patients who had reported to the department of oral and maxillofacial surgery, college of dental science and hospital, Rau, Indore, India for extraction of teeth during COVID pandemic time period of 15 months from April 2020 to June 2021. Extraction procedure was done for all these patients, taking into consideration patient’s age, gender, type of teeth and the reason for extraction. Results: A total of 906 teeth were extracted in 769 patients. Females outnumbered males in both total number of patients and number of teeth extracted. Dental caries was the main reason for extraction of teeth, followed by periodontitis, impacted teeth, teeth extraction for orthodontic purposes, malposed, supernumerary teeth and others. Conclusions: Dental caries and periodontitis were the two main reasons for extraction of teeth in Corona pandemic times.